Using cultural capital as a resource for negotiating participation in a teacher community of practice: a case study - Suriamurthee Maistry (Perspectives in Education, 2010)
Continuing professional development (CPD) initiatives for teachers in South Africa take on various forms, ranging from formalised, structured, credit-bearing certification programmes to informal, relatively unstructured, situated learning programmes. While many formal programmes can claim success by measuring throughput rates, there is still much to learn about how and why teachers participate in CPD programmes in the way they do. In fact, CPD planners seldom take into consideration teacher biographies and the socio-economic contexts within which teachers work. This article examines the influence of biography and context on the nature of participation and learning in a teacher community of practice. It uses data from the Teaching Economic and Management Sciences (TEMS) teacher development programme and focuses on the experiences of a novice EMS teacher as he engages with the challenge of curriculum development. Drawing on the work of Wenger (1998), Bourdieu (1992) and Yosso (2005), it is argued that cultural capital has a significant influence on a teacher’s ability to negotiate participation in a community of practice. This interpretative case study draws on tenets of symbolic interactionist ethnography (Woods, 1996) to guide the research process.